Distribution of Lithuanian publications by J. Zavadzkis firm 1805-1864 - Navickienė, Aušra (Knygotyra, 2024)
J. Zavadzkis’ firm—one of the largest printing, publishing, and distributing firms in Lithuania—was the most important enterprise in the publishing and trade of Lithuanian books in the 19th century. The extent of the Zavadzkis family’s trade in Lithuanian books directly depended on the publishing activity of the firm. The passive publication of Lithuanian books in the period of 1805-1852 resulted in a minimal extent of Lithuanian books sold. It didn’t reach 1% of book sales during the period described. The trade of Lithuanian books became very active in 1853-1864, during the years of intensive publishing of Lithuanian books, when one-third of all books printed at that time appeared from the firm. In addition to the bookshop in Vilnius, which had been in operation since 1805, a bookshop in Varniai was established in 1853. The bookshop in Varniai, being located in the center of Lithuanian democratic culture and the most Lithuanian and literate part of Lithuania, became a very important center for the distribution of Lithuanian books. The extent of trade at the bookshop in Varniai was larger than that in Vilnius. In 1853-1864, the bookshop in Vilnius sold about 16,000 copies of Lithuanian books, while 280,000 copies were sent to Varniai. There were 45 titles of books published by the Zavadzkis family. There were also publications by L. Ivinskis, S. Daukantas, M. Valančius, and M. Akelaitis. The number of Lithuanian book titles compared with titles in other languages was very small in both the Vilnius and Varniai bookshops due to second editions or large print runs. Customers acquired books in different ways; trade "by counter" was not very popular. Small traders engaged in commission trade often resold books to the main customers, who were peasants. Book sales particularly thrived at annual fairs in various towns and small towns across Lithuania. The fairs in Šiluva and Kalvarijos were particularly famous, and special shipments from the Vilnius bookshop were arranged for them. Other customers, such as office employees, doctors, teachers, chemists, and clergy from different regions, often subscribed to books and received them by mail. The customers of the bookshops were spread throughout Žemaičių and Vilnius dioceses. J. Zavadzkis’ firm used book advertisements by making bibliographical lists of books and printing them on book covers or in separate publications. In 1858, the first trade bibliographical publication appeared in Greater Lithuania.